Effects of combined nutrient and water stress on the growth of Hopea odorata Roxb. and Mimusops elengi linn. Seedlings / Siti Rubiah Zainudin, Kamis Awang and Ahmad Husni Mohd. Hanif - Zainudin, Siti Rubiah; Awang, Kamis; Mohd. Hanif, Ahmad Husni (2002)
The growth of Hopea odorata and Mimusops elengi seedlings under drought and various fertilisation rates under nursery condition was investigated. Both H. odorata and M. elengi seedlings responded differently to fertiliser application and drought. Application of slow release fertiliser (Best Tab, 20:10; 5 NPK) at 30 and 50g promoted greater height growth for H. odorata and M. elengi seedlings respectively. M. elengi seedlings were able to tolerate high fertiliser application (50g), with increased in height but thinner diameter and apparently is not suitable for urban planting. Growth of H .odorata seedlings was greatly promoted through application of 30g under well-watered condition (F3WO) resulting in a much more balanced growth in terms of shoot and root ratio which is vital for plants growing in the harsh urban environment where competition for water and nutrient which is usually very intense.